Prevalence of lifetime self-injurious thoughts and behaviors in a global sample of 599 patients reporting prospectively confirmed diagnosis with premenstrual dysphoric disorder - Eisenlohr-Moul, Tory A.; Divine, Madeline; Schmalenberger, Katja; Murphy, Laura; Buchert, Brett; Wagner-Schuman, Melissa; Kania, Alyssa; Raja, Sabina; Miller, Adam Bryant; Barone, Jordan; Ross, Jaclyn (BMC psychiatry, 2022)
Suicide is the second leading cause of death among Americans ages 10 to 34, with alarming recent increases in suicide rates among those assigned female at birth. A large body of evidence points to menstrual cycle influences on self-injurious thoughts and behaviors (STBs), suggesting that neurobiological hormone sensitivities, such as in premenstrual dysphoric disorder (PMDD), may drive suicide risk in females. However, existing studies of STBs in PMDD use cross-sectional self-report measures of PMDD with poor validity. As a first step to establish accurate prevalence rates of STBs in PMDD, we examined the lifetime prevalence of STBs in a large global survey of patients reporting a diagnosis of PMDD based on daily ratings.
Gesehen am 25.05.2022